Radiological Interventions in Obstetrics and Gynaecology - Reidy, John; Hacking, Nigel; McLucas, Bruce (Diagnostic Imaging, 2014)
This book provides a state-of-the-art review of the technical and clinical aspects of the vascular interventional radiological (IR) procedures currently employed in obstetrics and gynaecology. A particular focus is on uterine artery embolisation for fibroid disease, which is contrasted with the main alternative uterus-conserving surgical approach of myomectomy, and with ablation therapy. Detailed consideration is also given to the role of embolisation in a variety of other less common conditions, including arteriovenous malformations, post-partum haemorrhage, abnormal placentation and pelvic congestion syndrome. IR procedures are examined from a critical gynaecological perspective and with regard to surgical alternatives. The authors include leading interventional radiologists and gynaecologists from the United Kingdom, Europe and North America.  .